Strategi Personal Branding Aktor Politik Ferdiansyah Anggota DPRD Tanggerang Selatan melalui Instagram - alam, cholidi asadil (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Article history Received Revised Accepted The use of social media by political actors to enhance public confidence in themselves and to establish a public image Politicians' personal branding on social media will affect people's impressions of themselves and make it easier for them to communicate politically. Ferdiansyah is a political actor who is a member of the South Tangerang DPRD and uses social media to communicate with the public. Instagram is a social media platform that allows users to interact in two directions. Ferdiansyah uses it to establish personal branding by expressing his personality from each upload, which will make it simpler for him to communicate with his community on political issues. This article discusses Ferdiansyah's personal branding approaches, which are based on four personal branding formation and development strategies. A descriptive qualitative methodology is used in this research. According to the result of this research, Ferdiansyah has implemented four successful personal branding strategies in order to bring him closer to the community and strengthen his credibility.